PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI INDOMARET CABANG PERMATA PAMULANG TANGERANG SELATAN - Wawan Kurniawan Wawan; suworo suworo (Jurnal Sinergi Manajemen, 2024)
ABSTRACK The purpose of this research is to find out whether there is an influence of promotions and service quality on consumer purchasing decisions at the Indomaret branch of Permata Pamulang, South Tangerang. This type of research uses an associative and quantitative approach in collecting samples using simple random sampling techniques. This research was conducted on consumers of the Indomaret Permata Pamulang branch. The sampling technique used the Slovin formula and a sample of 100 respondents was obtained. Based on partial research results (t test), it was concluded that promotions had a positive and significant effect on purchasing decisions by obtaining a calculated t value > t table or (11.349 > 1.984) and reinforced by a value of ρ alue < Sig. 0.050 or (0.000 < 0.050). Meanwhile, partially service quality has a positive and significant effect on purchasing decisions with the calculated t value > t table or (11.572 > 1.984) and is strengthened by the value ρ alue < Sig.0.050 or (0.000 < 0.050). Based on simultaneous hypothesis testing (F Test), the resulting promotion and service quality variables have a positive and significant effect on purchasing decisions with the calculated F value > F table or (67.372 > 2.308), this is also reinforced by ρ alue < Sig.0.050 or ( 0.000 < 0.050). Keywords: Promotion, Service Quality and Purchasing Buying